Standing and Responding in Solidarity with Disenfranchised Immigrant Families in the United States: An Ongoing Call for Action. (3rd November 2020) - Wieling, Elizabeth; Trejo, Andrea N.; Ellen Patterson, Jo; Weingarten, Kaethe; Falicov, Celia; Hernández, Ana V.; Cook Heffron, Laurie; Faulkner, Monica; Rubén Parra‐Cardona, José
Abstract : The status of immigrant families resettled to the United States in the past decade has been fraught with upsurges of governmental policies that have systematically increasing the levels of oppression, violence, and abuses of human rights. The socio‐political‐economic toll of xenophobic practices on specifically targeted immigrant populations is magnified by the psychological and relational impact they have on individuals, families, and communities. This manuscript is conceptualized as an ongoing call for social action and specific mobilization by mental health professionals in response to the increasing threats to civility and dignity faced by various immigrant communities. The paper is organized in three sections: (a) an overview of the effects of immigration policy on immigrant family experiences; (b) the impact of mental and relational health on immigrant populations; and (c) elaborations of three exemplar community projects designed to support immigrant families. The manuscript concludes with a discussion exploring avenues for promoting a stronger base for solidarity and social action.